Genome-wide association study reveals candidate genes influencing lipids and diterpenes contents in Coffea arabica L - Sant'Ana, Gustavo C.; Pereira, Luiz F. P.; Pot, David; Ivamoto, Suzana T. [UNESP]; Domingues, Douglas S. [UNESP]; Ferreira, Rafaelle V.; Pagiatto, Natalia F.; Silva, Bruna S. R. da; Nogueira, Livia M.; Kitzberger, Cintia S. G.; Scholz, Maria B. S.; Oliveira, Fernanda F. de; et al. (Nature Publishing Group, 2018)
Lipids, including the diterpenes cafestol and kahweol, are key compounds that contribute to the quality of coffee beverages. We determined total lipid content and cafestol and kahweol concentrations in green beans and genotyped 107 Coffea arabica accessions, including wild genotypes from the historical FAO collection from Ethiopia. A genome-wide association study was performed to identify genomic regions associated with lipid, cafestol and kahweol contents and cafestol/kahweol ratio. Using the diploid Coffea canephora genome as a reference, we identified 6,696 SNPs. Population structure analyses suggested the presence of two to three groups (K = 2 and K = 3) corresponding to the east and west sides of the Great Rift Valley and an additional group formed by wild accessions collected in western forests. We identified 5 SNPs associated with lipid content, 4 with cafestol, 3 with kahweol and 9 with cafestol/kahweol ratio. Most of these SNPs are located inside or near candidate genes related to metabolic pathways of these chemical compounds in coffee beans. In addition, three trait-associated SNPs showed evidence of directional selection among cultivated and wild coffee accessions. Our results also confirm a great allelic richness in wild accessions from Ethiopia, especially in accessions originating from forests in the west side of the Great Rift Valley.